Falls from ladders in Australia: comparing occupational and non‐occupational injuries across age groups. (24th October 2016) - Vallmuur, Kirsten; Eley, Rob; Watson, Angela
Abstract: Objective : To examine national ladder‐related fall injury patterns and trends, and compare the changes over time in occupational and non‐occupational falls across age groups. Methods : Analysis of national hospital morbidity data to examine trends over time and differences between groups. Results : There were 41, 092 hospitalised falls from ladders in Australia over the ten year period from July 2002 to June 2012, rising from 3, 374 hospitalisations in 2002/03 to 4, 945 hospitalisations in 2011/12. The age standardised rate of ladder‐related fall hospitalisations rose significantly for males, and a higher increase was evident in people aged over 60 years. Occupational falls accounted for 20% of hospitalisations, and the hospitalisation rate for both occupational and non‐occupational falls increased significantly over the ten year period. Conclusions : With almost 5, 000 hospital admissions per year in recent years and a significant rise in the rate of hospitalisations over the past decade, this paper highlights the importance of focusing injury prevention efforts to reduce the growing number of ladder‐related falls. Implications : This study demonstrates the significant burden that ladder‐related falls are continuing to have on the community, both in the occupational and domestic setting.